Internationalisation of the Study of Religion and Its Methodological Challenges - AKRAM , MUHAMMAD (Islamic Studies, 2019)
This paper discusses internationalisation of the study of religion after the mid-twentieth century and some methodological implications of this development. It is shown that when the International Association for the History of Religions (IAHR) was established in 1950 under the auspices of UNESCO to collaborate between scholars from different parts of the world, some non-Western scholars raised questions about the exact nature and objectives of the study of religion. The then protagonists of IAHR quickly responded to these questions by proclaiming “the basic minimum conditions” for academic study of religion, which did not leave much space for diversity of cultural perspectives in the field. Then the paper shows, through a brief historical survey of relevant materials, how the increased interaction between scholars from different cultures of the world thenceforth exposed the Eurocentric tenor of this discipline, and by implication its assumed methodological universality also came under question. It is concluded that, in spite of the widespread recognition of methodological contingencies afforded by different cultural perspectives and regional contexts, scholars are still divided on how various knowledge traditions of the world can be accommodated in the discipline without succumbing to explicit biases or apologetics.